Exploring perceptions of group antenatal Care in Urban India: results of a feasibility study - R. Rima Jolivet; Bella Vasant Uttekar; Meaghan O'Connor; Kanchan Lakhwani; Jigyasa Sharma; Mary Nell Wegner (BMC, 2018)
Abstract Background Making high-quality health care available to all women during pregnancy is a critical strategy for improving perinatal outcomes for mothers and babies everywhere. Research from high-income countries suggests that antenatal care delivered in a group may be an effective way to improve the provision, experiences, and outcomes of care for pregnant women and newborns. A number of researchers and programmers are adapting group antenatal care (ANC) models for use in low- and middle-income countries (LMIC), but the evidence base from these settings is limited and no studies to date have assessed the feasibility and acceptability of group ANC in India. Methods We adapted a "generic" model of group antenatal care developed through a systematic scoping review of the existing evidence on group ANC in LMICs for use in an urban setting in India, after looking at local, national and global guidelines to tailor the model content. We demonstrated one session of the model to physicians, auxiliary nurse midwives, administrators, pregnant women, and support persons from three different types of health facilities in Vadodara, India and used qualitative methods to gather and analyze feedback from participants on the perceived feasibility and acceptability of the model. Results Providers and recipients of care expressed support and enthusiasm for the model and offered specific feedback on its components: physical assessment, active learning, and social support. In general, after witnessing a demonstration of the model, both groups of participants-providers and beneficiaries-saw group ANC as a vehicle for delivering more comprehensive ANC services, improving experiences of care, empowering women to become more active partners and participants in their care, and potentially addressing some current health system challenges. Conclusion This study suggests that introducing group ANC would be feasible and acceptable to stakeholders from various care delivery settings, including an urban primary health clinic, a community-based mother and child health center, and a private hospital, in urban India.